The adverse selection effect of corporate cash reserve: Evidence from acquisitions solely financed by stock - Gao, Ning (Journal of Corporate Finance, 2011)
Corporate cash reserve has an adverse selection effect. Specifically, if investors know a company does not have to issue to invest, an attempt to do so sends a strong signal of overvaluation. This notion has not been explicitly studied in the extant empirical literature, despite its intuitiveness. Using a sample of acquisitions solely financed by stock to exclude the potential complications of free cash flow, I find that announcement returns are lower for a bidder with a higher excess cash reserve. This effect is stronger in hot equity market years or when a bidder's standalone value is more difficult to evaluate. I also find evidence supporting the idea that targets request cash payment to remove “lemon” bidders in normal (non-hot equity market) years, but accept too many stock offers in hot equity market years. After acquisitions, high-excess-cash-reserve bidders operationally outperform low-excess-cash-reserve bidders. Further, they spend more funds on reducing debt but not more on investments, compared with low-excess-cash-reserve bidders. Combined, these results show that cash reserve has information costs. Further, they highlight the importance of the two-sided information asymmetry framework of Rhodes-Kropf and Viswanathan (2004) in describing merger outcomes without resorting to behavioral or agency explanations.